Isolation of TRPV1 independent mechanisms of spontaneous and asynchronous glutamate release at primary afferent to NTS synapses - Fenwick, Axel J.; Wu, Shaw-wen; Peters, James H. (Frontiers in Neuroscience, 2014)
Cranial visceral afferents contained within the solitary tract (ST) contact second-order neurons in the nucleus of the solitary tract (NTS) and release the excitatory amino acid glutamate via three distinct exocytosis pathways; synchronous, asynchronous, and spontaneous release. The presence of TRPV1 in the central terminals of a majority of ST afferents conveys activity-dependent asynchronous glutamate release and provides a temperature sensitive calcium conductance which largely determines the rate of spontaneous vesicle fusion. TRPV1 is present in unmyelinated C-fiber afferents and these facilitated forms of glutamate release may underlie the relative strength of C-fibers in activating autonomic reflex pathways. However, pharmacological blockade of TRPV1 signaling eliminates only ~50% of the asynchronous profile and attenuates the temperature sensitivity of spontaneous release indicating additional thermosensitive calcium influx pathways may exist which mediate these forms of vesicle release. In the present study we isolate the contribution of TRPV1 independent forms of glutamate release at ST-NTS synapses. We found ST afferent innervation at NTS neurons and synchronous vesicle release from TRPV1 KO mice was not different to control animals; however, only half of TRPV1 KO ST afferents completely lacked asynchronous glutamate release. Further, temperature driven spontaneous rates of vesicle release were not different from 33 to 37°C between control and TRPV1 KO afferents. These findings suggest additional temperature dependent mechanisms controlling asynchronous and thermosensitive spontaneous release at physiological temperatures, possibly mediated by additional thermosensitive TRP channels in primary afferent terminals.